Enquitreídeos (Enchytraeidae, Oligochaeta) como indicadores do manejo do solo e em ensaios ecotoxicológicos - Assis, Orlando (2015)
Agriculture occupies a large area of the Brazilian territory, interacting with the major biomes. Soil management, the use of pesticides and fertilizers can contribute to the imbalance of the biota, the soil fauna, impacting the harmony of the whole soil ecosystem. The soil disturbance in plowing and disking exposes the soil fauna to the sun' radiation, which can be harmful to of species in this environment. Synthetic fertilizers can unbalance levels of soil nutrients, directly impacting the dynamics of organisms. The pesticides can be deleterious to the living organisms in the soil. This study aims to evaluate potential of the enchytraeids as soil management indicators in areas of horticulture and grain farming and to identify which factors influence the abundance and diversity of these worms in different land use systems (SUS); It also aims to assess the potential of the enchytraeids to respond to the natural soil quality of the areas of study and the toxicity of recommended doses of the most used pesticide (glyphosate) in laboratory tests; Four land use systems (SUS) in Quitandinha – PR were chosen for the present study: Organic Vegetable Crops (OO), Conventional Vegetable Crops (OC) and Conventional tillage (LC), Native Forest (FN) with true repetitions. The abundance of enchytraeids was statistically higher in FN than LC, while the richness of genera reduced from six to two, respectively. Among the soil attributes, forest areas had lower pH, organic matter, nitrogen and higher potassium than other SUS in the other SUS and lower amount of phosphorus than the areas of conventional tillage. In ecotoxicological tests under laboratory conditions the number of juveniles of Enchytraeus sp produced in soil of the areas studied for 21 days of incubation were higher in soils from FN than LC. in agreement to field abundance data. Ecotoxicological tests with gliphosate in concentrations based on doses used by the agricultures in the area sudied showed that in artficial soil, even concentrations equivalent to recommended doses may reduce reproduction significantly, suggesting this popular herbicide may be harmful to enchytraeids and should be used with caution. The results suggest the abundance and richness of genera are good indicators of soil use systems in the area studied and that the autochthonous enchytraeid Enchytraeus sp responded well to laboratory tests to evaluate soil quality.